Insights into the putative role of leptin in various traversing stages of women: A narrative review - G. M. Saranya,M. Ramesh Pathy (Journal of Applied Pharmaceutical Science, 2018)
From adolescence to adulthood, a woman goes through distinct phases in her life. The role of leptin in this journey is very crucial, as it supports her to cross different milestones in time. Leptin is an indispensable factor in the metabolic control of puberty, fertility, and pregnancy. Puberty is a chronic biological process that helps transform a child into an adult. In this process, sufficient amount of leptin is necessary for the initiation of puberty in girls. Apart from maintaining the energy homeostasis by regulating the food intake and energy expenditure, it also regulates various other hormones required for reproduction and regulation of the endocrine system. Malfunction of leptin alters the neuroendocrine pathways and causes a detrimental effect on reproductive disorders, such as PCOS, obesity, diabetes, anorexia, and infertility which are the most important intimation for female reproductive health worldwide. In this article, we aim to provide a synoptic view on the roles of leptin in the metabolic regulation of the reproductive axis, its hormonal regulations, permissive role for the onset of puberty, continuity of menstrual cycle and the putative roles of leptin during gestation, including its potential function as placental hormone in a female.
Keywords: Leptin,puberty,fertility,energy homeostasis,obesity,pregnancy,menopause.